Pengaruh Latihan Fleksi William Terhadap Tingkat Nyeri Punggung Bawah Pada Lansia Di Unit Pelayanan Terpadu Sosial Tresna Werdha Blitar Di Kabupaten Tulungagung - Hanik, Umi; Lasman, Lasman; Nurhidayati , Nurhidayati; Sukanto, Sukanto (Universitas Muhammadiyah Sidaorjo, 2024)
Old age is a factor that aggravates the occurrence of lower back pain due to the decline in body functions, especially bone. William's flexion exercise is one of the therapeutic exercises for lower back pain sufferers by strengthening the abdominal muscles and maximus gluteus muscles as well as stretching the extensor muscles of the back. The purpose of this study was to know the effect of William flexion training on lower back pain levels in the elderly In Blitar Age Blind Social Service Unit at Tulungagung Dormitory. This research uses Pre pre-experimental design by using model one group pre-test – post-test design. The population of this study were all elderly at UPT Social Service of Tresna Werdha Blitar Tulungagung Dormitory who experienced low back pain, the sample was taken with a total sampling technique of 33 respondents. The variable of therapy-free William flexion, the dependent variable of lower back pain. The study was conducted on March -April a processing using a Wilcoxon signed rank test with SPSS program. The result of the research was obtained before the therapy of William's flexion. Most of the respondents had severe back pain, 19 respondents (57.6%) and after the therapy of William's flexion, almost all respondents had mild back pain as many as 27 respondents (81.8%). The result of the statistic test of Wilcoxon signed rank by using the SPSS program got result P Value = 0,000 <0,05 so H1 accepted, which means there is an influence of William flex exercise to lower back pain level at elderly in Technical Service Unit of Tresna Werdha Blitar at Tulungagung year 2018. William's flexion exercises will increase muscle elasticity so that it will reduce pain and restore work to some muscle groups. William's flexion movement is done slowly and rhythmically so that it will stimulate the sensory nerve fibers that will inhibit the activation of pain receptors in Tresna Werdha Blitar Tulungagung Hostel